PENGGUNAAN CERITA ANAK SEBAGAI MEDIA PENINGKATAN KEMAMPUAN BERBAHASA INDONESIA SISWA KELAS 5 SEKOLAH DASAR - Dyah Werdiningsih (LITERA, 2009)
This study aimed to describe the use of children’s stories as media to improve Indonesian language skills of Year 5 elementary school students. This study was an action research study employing the qualitative approach. The design was based on the procedure proposed by Kemmis and McTaggart (1988), consisting of plan, action, observation, and reflection. The subjects comprised teachers and students of SDN Gadang I Malang. The results showed that the learning model using children’s stories in the Indonesian language learning was capable of improving Indonesian language skills of Year 5 elementary school students. This was shown by both their spoken and written performances.